Impact of ocean acidification on microzooplankton grazing dynamics - Wenting Shi; Wenting Shi; Wenting Shi; Xiaoting Fu; Xiaoting Fu; Xiaoting Fu; Yabo Han; Yabo Han; Yabo Han; Jiahui Qin; Jiahui Qin; Jiahui Qin; et al. (Frontiers in Marine Science, 2024)
This study examines the potential impacts of projected atmospheric carbon dioxide (pCO2) levels reaching 800 ppm by the end of the century, focusing on ocean acidification effects on marine ecosystems in the coastal areas of Bohai. We investigated how acidification affects the grazing patterns of microzooplankton using dilution techniques and ecophysiological methods. Our findings indicate that acidic conditions shift the phytoplankton community structure, changing dominant species. Elevated CO2 concentrations reduced grazing pressure on phytoplankton, with less steep declines in growth rates at 800 ppm CO2 (spring: 2.43 d−1 vs. 2.16 d−1, summer: −0.46 d−1 vs. −0.73 d−1, autumn: −0.45 d−1 vs. −0.90 d−1) and significant decreases in grazing pressure percentages (%Pp from 0.84 to 0.58 and %Pi from 0.64 to 0.46). Short-term acid exposure significantly increased superoxide dismutase activity in both microplankton (from 0.03 to 0.08 U mg−1, p<0.01) and nanoplankton (from 0.05 to 0.09 U mg−1, p<0.001), indicating an adaptive response to oxidative stress. These results highlight that elevated CO2 levels primarily boost phytoplankton growth by reducing microzooplankton grazing pressure, resulting in higher growth rates and a shift towards smaller-sized phytoplankton, reflecting complex short-term ecological responses to acidification. Further research is needed to understand the long-term effects of ocean acidification on microzooplankton and their role in marine secondary productivity.